Experimental investigation of the effect of different process variables on the viscosity of sulfonated polyacrylamide copolymers - Akbari, S. (Springer Verlag, 2017)
Increasing the viscosity of injected water by the addition of polymer improves the displacement efficiency during the water flooding process. In this study, a sulfonated polyacrylamide copolymer has been added to salt water. Several parameters, such as polymer concentration, shear rate, NaCl concentration, molecular weight and sulfonation degree, have a significant effect on the polymer solution viscosity. The main objective of this paper is to investigate how the polymer solution viscosity varies with changes in the input parameters so as to identify the relative importance of these parameters. This paper incorporates the Design of Experiments technique using Taguchi’s method and the Analysis of Variance (ANOVA) to investigate the effect of process variables on the viscosity of a polymer solution. Five input parameters and six possible interactions have been investigated. The analysis of the experimental results revealed that two input parameters, namely, polymer concentration and shear rate, have the most significant impact on polymer viscosity. Two strong interactions were observed in the (1) NaCl concentration and sulfonation degree and (2) molecular weight and NaCl concentration studies. The results show that the Taguchi method was successful in identifying the main effects and interaction effects. ANOVA further buttresses the results from Taguchi’s method by showing a strong similarity in its results. © 2016, The Author(s).